Polyvalent HIV-1 Env vaccine formulations delivered by the DNA priming plus protein boosting approach are effective in generating neutralizing antibodies against primary human immunodeficiency virus type 1 isolates from subtypes A, B, C, D and E - Wang, Shixia; Pal, Ranajit; Mascola, John R.; Chou, Te-Hui W.; Mboudjeka, Innocent; Shen, Siyuan; Liu, Qin; Whitney, Stephen; Keen, Timothy; Nair, B.C.; Kalyanaraman, V.S.; Markham, Philip; et al. (Virology (New York, N.Y.), 2006)
A major challenge in developing an HIV-1 vaccine is to identify immunogens and their delivery methods that can elicit broad neutralizing antibodies against primary isolates of different genetic subtypes. Recently, we demonstrated that priming with DNA vaccines expressing primary HIV-1 envelope glycoprotein (Env) followed by recombinant Env protein boosting was successful in generating positive neutralizing antibody responses against a clade B primary HIV-1 isolate, JR-FL, that was not easily neutralized. In the current study, we examined whether the DNA priming plus recombinant protein boosting approach delivering a polyvalent primary Env formulation was able to generate neutralizing antibodies against primary HIV-1 viral isolates from various genetic subtypes. New Zealand White rabbits were first immunized with DNA vaccines expressing one, three or eight primary HIV-1 gp120 antigens delivered by a gene gun followed by recombinant gp120 protein boosting. Neutralizing antibody responses were examined by two independently executed neutralization assays: the first one was a single round infection neutralization assay against a panel of 10 primary HIV-1 isolates of subtypes A, B, C and E and the second one used the PhenoSense assay against a panel of 12 pseudovirues expressing primary HIV-1 Env antigens from subtypes A, B, C, D and E as well as 2 pseudoviruses expressing the Env antigens from MN and NL4-3 viruses. Rabbit sera immunized with the DNA priming plus protein boosting approach, but not DNA vaccine alone or Env protein alone, were capable of neutralizing 7 of 10 viruses in the first assay and 12 of 14 viruses in the second assay. More importantly, sera immunized with the polyvalent Env antigens were able to neutralize a significantly higher percentage of viruses than the sera immunized with the monovalent antigens. Our results suggest that DNA priming followed by recombinant Env protein boosting can be used to deliver polyvalent Env-antigen-based HIV-1 vaccines to elicit neutralizing antibody responses against viruses with diverse genetic sequence variations.